The relationship between weight-adjusted-waist index and total bone mineral density in adults aged 20-59 - Guo, Meiqian; Lei, Yi; Liu, Xueqing; Li, Xiang; Xu, Yong; Zheng, Donghui (Frontiers in Endocrinology, 2023)
Introduction: According to reports, obesity has a significant impact on bone health. And the weightadjusted-waist index (WWI), superior to BMI and waist circumference (WC), is a new obesity indicator arising in recent years. This research investigated the relationship between WWI and total bone mineral density (BMD) for adults aged 20 to 59.Methods:Using data from the 2011-2018 NHANES, we looked into the independent link between WWI and total BMD as well as its nonlinearity using weighted multivariate logistic regression and smooth curve fitting. Two-stage linear regression models were employed to calculate the threshold effects. There were additional subgroup analyses and testing for interactions.:Multiple linear regression studies on a total of 10,372 individuals showed a significant inverse link between WWI and total BMD in adults between 20 and 59 [β = -0.04, 95% CI: (-0.04, -0.03), P<0.0001]. And smoking, race, and CKD had no significant effect on this negative connection (P for interaction >0.05 ). In addition, we found a nonlinear relationship between WWI and total BMD in diabetic and chronic kidney disease patients, for which the saturation point was 11.38 cm/√kg in the chronic kidney disease patient group and 10.29 cm/√kg in the diabetic patient group.Conclusions: Our analysis demonstrated a significant inverse association between WWI and total BMD in adults aged 20-59.